Thionated levofloxacin derivative: Potential repurposing for cancer treatment and synergism with doxorubicin on doxorubicin-resistant lung cancer cells - Hamza Abumansour; Osama H. Abusara; Mohammad Abu-Sini; Wiam Khalil; Ali I. M. Ibrahim; Amal M. Badawoud; Majed S. Al Yami; Dina H. Abulebdah; Shiraz Halloush (PLoS ONE, 2025)
Objectives Fluoroquinolones, such as levofloxacin (LVX), are extended-spectrum drugs used for the treatment of bacterial infections. Several fluoroquinolone derivatives have shown promising antibacterial and anticancer activities. Our group has earlier synthesized and investigated thionated LVX analogs, compounds 2 and 3, on A549 (non-small cell lung cancer) cell line and showed promising anticancer activity. The mechanism of cytotoxicity may be, in part, via aldehyde dehydrogenase enzyme inhibition and antioxidation. In this study, compounds 2 and 3 were evaluated on prostate (PC-3), breast (MCF7), colorectal (Caco-2), and small cell lung cancer (H69 and H69AR) cell lines. Methods The anticancer activity was measured using resazurin colorimetric method. Combination treatments with doxorubicin (DOX) were also employed and combination index (CI) value were calculated. Results Compound 3 possessed higher anticancer activity compared to compound 2 on the tested cancer cell lines. Compound 3 had the highest activity on PC-3 cells with IC50 value of 3.58 µM. DOX was also tested for comparison and had IC50 value of less than 0.5 µM in all tested cell lines except for H69AR (DOX-resistant form of H69), which was 4.62 µM. Combination treatment with DOX resulted in significant reduction of cell viability in PC-3, H69, and H69AR cells, with those on H69 and H69AR cells resulted in additive (CI = 1.0) and synergistic effects (CI = 0.6), respectively. Conclusions Compound 3, a thionated LVX derivative, showed a promising anticancer activity, prompting its potential repurposing for cancer treatment as well as combination treatment with DOX on DOX-resistant cancer cells.